2017
DOI: 10.1002/app.44991
|View full text |Cite
|
Sign up to set email alerts
|

Nonisocyanate thermoplastic polyurethane elastomers based on poly(ethylene glycol) prepared through the transurethanization approach

Abstract: Nonisocyanate thermoplastic polyurethane elastomers (NIPUs) were synthesized with the transurethanization approach. Dimethyl dicarbamates (DCs) were prepared by the reaction of a diamine with an excess of dimethyl carbonate in the presence of 1,5,7‐triazabicyclo[4.4.0]dec‐5‐ene (TBD) as a catalyst. Then, the polymers were obtained under neat conditions through the reaction of DC with polyethyleneglycol of average molecular weight of 1500 g/mol (PEG1500) at variable temperatures in the presence of different amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…The substitution of carcinogenic, mutagenic and reprotoxic (CMR) compounds, the reduction of VOC emissions and the study of novel properties, provided eco-friendly alternatives which are described in this part. 140 These NIPUs can be formed by different approaches, such as transurethanization, [141][142][143] ring opening polymerization, 144,145 or various rearrangements, 146 but the most promising route seems the polyaddition between diamines and cyclic carbonates, 147 including biobased resources. 148 Poly(alkyd-urethane) synthetized from DFF showed better hardness, adhesion and chemical resistance than those formed with CHDA.…”
Section: Further Perspectives On Sustainable Alkyd Hybridsmentioning
confidence: 99%
“…The substitution of carcinogenic, mutagenic and reprotoxic (CMR) compounds, the reduction of VOC emissions and the study of novel properties, provided eco-friendly alternatives which are described in this part. 140 These NIPUs can be formed by different approaches, such as transurethanization, [141][142][143] ring opening polymerization, 144,145 or various rearrangements, 146 but the most promising route seems the polyaddition between diamines and cyclic carbonates, 147 including biobased resources. 148 Poly(alkyd-urethane) synthetized from DFF showed better hardness, adhesion and chemical resistance than those formed with CHDA.…”
Section: Further Perspectives On Sustainable Alkyd Hybridsmentioning
confidence: 99%
“…One important advantage of methanolysis is the production of O -methylcarbamate, a useful reactive intermediate that can be used to regenerate PUs through transcarbamoylation associated to the release of MeOH which can be easily eliminated by evaporation during the reaction. We tried to achieve repolymerization to prepare PU by using the dicarbamate 2a and PTMO (2000); they were subjected to transcarbamoylation, with an organic base TBD to catalyze the reaction . The results are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Transcarbamoylation can be used as well to synthesize PUs to avoid the use of toxic isocyanates. Recent works have shown that transcarbamoylation is an efficient reaction and can be operated in mild conditions with a soft base at low temperatures (<70 °C) offering promising perspectives in the field of PU recycling . Here, we investigate a recycling procedure involving the depolymerization of PU wastes producing dicarbamates and polyols coupled to the repolymerization of these intermediates to regenerate new PUs both using transcarbamoylation reaction in mild conditions (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…DMC is a widely used non-toxic reagent, which does not require special protective measures for irritation or mutagenic effects caused by contact or inhalation [ 23 , 24 , 25 ]. Kebir et al [ 26 ] prepared polyether-based polyurethanes from dimethyl carbonate, using polyethylene glycol as the soft segment and butylene glycol as the chain extender. The molecular weight (7500–14,800 g/mol) and melting point (38–48 °C) of the obtained polyurethanes are not high enough, making it difficult to meet the use application requirements.…”
Section: Introductionmentioning
confidence: 99%